The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1136/bcr-2018-227271
|View full text |Cite
|
Sign up to set email alerts
|

Porta hepatis abscess and portal vein thrombosis following ingestion of a fishbone

Abstract: A man in his late 50s presented to the emergency room with a 1-month history of severe abdominal pain and an endoscopic fishbone retrieval from his rectum. Serial CT scans revealed a fishbone located in the patient’s upper abdomen, which had migrated through the stomach wall, into the periportal space, causing a contained gastric perforation, development of a porta hepatis abscess and secondary portal vein thrombosis. Furthermore, the sharp tip of the fishbone lay 5 mm from the patient’s hepatic artery. He was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Revision of all published data on surgical management of liver FBs confirm that surgical extraction needs to be considered in all patients, mostly based on lessons learned from the adult literature [ 44 ]. Published experiences in adults have reported miscellaneous long-term complications related to retained FBs in the liver: delayed surgery may lead to liver abscess, hepatic granuloma, pseudotumor [ 2 , 6 , 7 , 8 ] or dislocation possibly causing biliary or vascular damage [ 9 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Revision of all published data on surgical management of liver FBs confirm that surgical extraction needs to be considered in all patients, mostly based on lessons learned from the adult literature [ 44 ]. Published experiences in adults have reported miscellaneous long-term complications related to retained FBs in the liver: delayed surgery may lead to liver abscess, hepatic granuloma, pseudotumor [ 2 , 6 , 7 , 8 ] or dislocation possibly causing biliary or vascular damage [ 9 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients are often completely asymptomatic but the persistence of a foreign material inside the parenchyma may cause severe complications, usually infections such as liver abscess, hepatic granuloma, pseudotumor [ 2 , 6 , 7 , 8 ] or dislocate even over the long-term, possibly causing biliary or vascular damage [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other complications caused by the migration of a fish bone through the stomach or duodenal wall were described: portal vein thrombosis [9], portal and hepatic abscess associated with portal vein thrombosis [10], liver abscess [11,12], pseudotumoral gastric lesions [13] or liver actinomycosis [14].…”
Section: Discussionmentioning
confidence: 99%
“…Geographic region also affects the frequencies and types of foreign bodies that are found. 4 Eastern countries, including all the Asian countries, have a different set of intestinal impactions risk; the most common foreign body retrieved are fish bones as Asian countries (and many countries along the Mediterranean) tend to eat fish and meats with the bones intact. A single institution report from Hong Kong found that fish bones are more commonly found in middle-aged women, similar to the patient described in this case.…”
mentioning
confidence: 99%
“…A single institution report from Hong Kong found that fish bones are more commonly found in middle-aged women, similar to the patient described in this case. 4 Of the foreign bodies that perforate the digestive tract, 83 per cent occur in the ileocecum. The second most common site of perforation is the recto-sigmoid colon.…”
mentioning
confidence: 99%